Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$e^{x^{3}}+7x$$ Here is what I have tried so far, $$y'=(e^{x^{3}})'+(7x)'$$ $$y'=3e^{x^{2}}e^x+7$$ $$y'=3e^{x^{3}+x}+7$$

I am supposed to find the second derivative but I believe I have already made a mistake. I am not sure how I would apply the chain rule to the $e^{x^{3}}$. I checked Wolframalpha and the derivative of $e^{x^{3}}$ was $$3e^{x^{3}}x^2$$ Did I leave out a step when I applied chain rule? I went over the problem a couple of times and couldn't catch my mistake.

share|cite|improve this question
The derivative of $e^{x^3}$ is $e^{x^3}\cdot 3x^2$, by the chain rule. Indeed, $f(x)=e^x$ has $f'(x)=e^x$ and $g(x)=x^3$ yields $g'(x)=3x^2$. So $(f\circ g)'(x)=f'(g(x))g'(x)$. – 1015 Mar 14 '13 at 2:37
up vote 2 down vote accepted

$$\frac d{dx}\left(e^{x^3}\right) = e^{x^3}\cdot \bigl(x^3\bigr)' = e^{x^3}\bigl(3x^2\bigr) = 3e^{x^3}x^2$$

This is by the chain rule, and for the exponential function, this gives us $$\frac d{dx}\left(e^{f(x)}\right) = e^{f(x)}f'x$$

Then for the second derivative, we can use the product rule (and the chain rule again):

So $$\frac {d^2}{dx}\left(e^{x^3}\right) = \frac{d}{dx}\Bigl(3e^{x^3}x^2\Bigr) = \Bigl(3e^{x^3}\Bigr)\Bigl(x^2\Bigr)' + x^2\Bigl(3e^{x^3}\Bigr)' = 6xe^{x^3} + 9x^4e^{x^3}$$

share|cite|improve this answer
Is $\frac d{dx}\left(e^{f(x)}\right) = e^{f(x)}f'x$ something I should memorize or is it derived from another rule? – Kot Mar 14 '13 at 2:50
It is derived from the chain rule $g(x) = e^x, \; f(x) = x^3, \;g(f(x)) = e^{f(x)} = e^{x^3}$. But it handy to make the connection with how this works for $e^{f(x)}$, as noted, since the derivative of the exponential function $e^x = e^x$. – amWhy Mar 14 '13 at 2:54
Ahh, I understand now. The $e$ was throwing me off. Thank you for the explanation! – Kot Mar 14 '13 at 3:00
You're welcome...I found it really handy to "memorize" (but first understand): $\frac d{dx}\left(e^{f(x)}\right) = e^{f(x)}f'x$, just for these sorts of problems, because the derivative of the exponential function is unlike that of any other function: generally a no-brainer for $e^x$, and fairly straightforward for deriving $e^{f(x)}$ – amWhy Mar 14 '13 at 3:04

let T be the second derivative of the function ,

then ,

T = $ 3 e^{x^3} [ 3x^4 + 2x ] $

share|cite|improve this answer
$+^{+^{+^{+}}}$ – Babak S. Jun 28 '13 at 5:42



I think you can now handle the summand $\,7x\,$

share|cite|improve this answer


$ f(x) = e^x $ and $ g(x) = x^3 $, so that your first term could be written $ f(g(x)) $. Then the derivative of the first term is

$ f'(g(x)) g'(x) = e^{g(x)} (3x^2) = e^{x^3} 3x^2 $

share|cite|improve this answer

Did you push the "Step-by-step solution" button in WolframAlpha? If you're accessing WolframAlpha from within Mathematica, you get as many pushes as you like - not just the three free ones. Here's the result inside Mathematica:

enter image description here

I think this makes it reasonably clear where the $3x^2$ came from.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.